Water-Soluble MMP-9 Inhibitor Reduces Lesion Volume after Severe Traumatic Brain Injury - Lee, Mijoon (ACS Chem Neurosci, 2015)
SB-3CT is a potent and selective inhibitor of matrix metalloproteinase (MMP)-2 and -9, which has shown efficacy in an animal model of severe traumatic brain injury (TBI). However, SB-3CT is poorly water-soluble and is metabolized primarily to p-hydroxy SB-3CT (2), a more potent inhibitor than SB-3CT. We synthesized the O-phosphate prodrug (3) of compound 2 to enhance its water solubility by more than 2000-fold. The prodrug 3 was a poor MMP inhibitor, but readily hydrolyzed to the active 2 in human blood. Pharmacokinetics and brain distribution studies in mice showed that 2 crossed the blood-brain barrier (BBB) and achieved therapeutic concentrations in the brain. The prodrug 3/compound 2 was evaluated in a mouse model of severe TBI and found to significantly decrease the brain lesion volume and improve neurological outcomes. MMP-9 inhibition by a water-soluble thiirane inhibitor is a promising therapy for treatment of TBI.